Städte und die beginnende Urbanisierung. Henri Lefebvre in der aktuellen Stadtforschung - Vogelpohl, Anne (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
In recent years, Henri Lefebvre’s theories have gained almost canonical status in urban and spatial studies, particularly in Anglophone countries. Although scholars often quote Lefebvre, his theories, however, tend to confuse due to their complexity and opaque language. By reconstructing his terminology through a close reading, this paper aims to interrogate the characteristics and dynamics of Lefebvre’s terms and their current relevance with regard to empirical and theoretical urban studies. Besides the frequently applied concept of the production of space, Lefebvre’s thesis on the urbanization of society is a prominent part of his works. But ambiguities remain between the terms “city” and “urban” as well as between actual societal realities and virtual possibilities. Following Lefebvre, the “city” is described as a historical condition and as having nearly vanished with industrialization. In contrast, the “urban” is posited as the emergent society consisting of differences, so that the notion of the urbanized society is intrinsically tied to the differential space within which it evolves. The discussion focuses on the dialectical movement between terms as an approach to potential empirical applications in urban and spatial studies. Additionally, this elaboration serves as a basis for continuing the necessary development of Lefebvre’s theories.
Keywords: Henri lefebvre; Urbanization; Production of space; Urban theory; Urban studies